Hydroxylation of progesterone by some Trichoderma species - El-Kadi, I A; Mostafa, M Eman (Folia microbiologica, 2004)
Thirty-three isolates belonging to six species of the genus Trichoderma were tested for the ability to hydroxylate progesterone to 11alpha-, 11beta-, 11alpha,17alpha- and 6beta, 17alpha-derivatives, and epicortisol. T. aureoviride, T. harzianum, T. polysporum and T. pseudokoningii produced 11alpha-hydroxyprogesterone. T. harzianum and T. hamatum can form only the 11beta-isomer. T. koningii and T. hamatum produced 11alpha-, 11beta-, 11alpha,17alpha- and 6beta,11alpha-hydroxy derivatives. 11alpha, 11beta, 6beta,11alpha- and 11alpha,17alpha-hydroxyprogesterones and epicortisol are produced by T. aureoviride and T. pseudokoningii. Cortisol was produced only when the medium was fortified by 10 g/L peptone. This is the first record of conversion of progesterone to mono-, di- and trihydroxyprogesterones by these Trichoderma species.